Prognostic value of endocapillary hypercellularity in IgA nephropathy patients with no immunosuppression - Chakera, Aron; MacEwen, C.; Bellur, S.; Chompuk, L.; Lunn, D.; Roberts, I. (2016)
Aim. Interpretation of retrospective clinicopathological studies of IgA nephropathy (IgAN) has been confounded by immunosuppression bias. In published validation studies of the Oxford Classification of IgAN, an average of 33% of patients received non-randomised steroid and/or cytotoxic therapy. In order to determine the true impact of proliferative lesions on the natural history of IgAN, analysis of patient cohorts that have received no immunosuppression is required. Methods. We performed a retrospective single centre study of patients with IgAN managed without immunosuppressive therapy. Biopsies were scored according to the Oxford Classification. The primary outcomes were renal survival or a rapid loss of renal function defined as a decline in eGFR of >5 ml/min/year. Results. 237 patients with IgAN were identified with a mean follow-up of 82 months. 200 had biopsies available for review, of which 156 were adequate for scoring using the Oxford Classification. 9/156 patients (5.8%) received some immunosuppressive therapy, mostly for unrelated conditions: these were excluded. In multivariate COX regression, including histological and clinical data, the only independent predictors of time to ESRD were baseline eGFR (HR 0.96 per ml/min increase, p = 0.018), baseline proteinuria (HR 1.36 per doubling, p = 0.004) and endocapillary hypercellularity (HR 4.75 for E1 compared to E0, p < 0.001). Independent predictors of a rapid decline in eGFR were proteinuria (OR 1.45 per doubling, p = 0.006), endocapillary hypercellularity (OR 3.41 for E1 compared to E0, p = 0.025) and tubular atrophy/interstitial fibrosis (OR 8.77 for T2 compared to T0, p = 0.006). Conclusions. In a cohort of IgAN patients receiving no immunosuppression, endocapillary proliferation and tubular atrophy/interstitial fibrosis are independent predictors of rate of loss of renal function. The lack of predictive value of E score in other clinicopathological studies is most likely a result of immunosuppression-associated bias. Our findings provide evidence to support immunosuppressive treatment of endocapillary-pattern IgAN.